Mendelian randomization highlights the causal association of obesity with periodontal diseases. (26th May 2022) - Dong, Jingya; Gong, Yixuan; Chu, Tengda; Wu, Lixia; Li, Sisi; Deng, Hui; Hu, Rongdang; Wang, Yi
Abstract: Aim: The underlying mechanisms connecting obesity and periodontal diseases remain unclear. This study investigates the potential causal association of obesity with periodontal diseases using Mendelian randomization (MR). Materials and Methods: Single‐nucleotide polymorphisms of obesity traits including body mass index (BMI), waist circumference (WC), and WC adjusted for BMI (WCadjBMI) from large‐scale genome‐wide association studies were screened for instrumental variables. The single trait periodontitis and the combined trait comprising periodontitis and loose teeth were adopted as surrogates for periodontal diseases. Inverse‐variance weighted (IVW), series of sensitivity analyses and multivariable MR were employed to determine the association of obesity with periodontal diseases. Results: IVW results showed that per 1‐SD increment in BMI (odds ratio, OR = 1.115; 95% confidence interval [CI] = 1.064–1.169; p  < .001) and WC (OR = 1.117; 95% CI = 1.052–1.185; p  < .001), but not WCadjBMI, were significantly associated with an increased risk of periodontitis/loose teeth. Moreover, the MR estimates were consistent across other MR sensitivity analyses and multivariable MR. However, a causal association of obesity with the single trait periodontitis was not identified. Conclusions: The presented evidence supports previous epidemiological findings by showing a potential causal association of genetic liability to obesity with periodontal diseases. The biological mechanisms underlying this association warrant further investigation.